Human-Terrestrial Wildlife Conflict in Ethiopia: A Systematic Review - Getahun Shanko; Bekele Tona (The Scientific World Journal)
We conducted a review of 26 articles published between 2009 and 2021 to determine human-wildlife conflict based on spatial and temporal patterns, biological components, drivers of conflict, and mitigation methods used. We employed search, synthesis, appraisal, and analysis framework for review and VOSviewer software for network analysis. We included articles that only focused on relations between terrestrial wildlife and humans, while others deal with ecology, distribution, and biology of wildlife because it does not go with HWC. Forty-seven species of terrestrial vertebrates were reported in conflict-related studies, being Bovidae and Cercopithecidae the most frequently studied groups, of which eleven are found in threatened list species. The main drivers reported were land use change, proximity to protected areas, and illegal resource exploitation. In the management case, the use of traditional protection techniques such as fencing, guarding, and physical barriers was reported. About 178 keywords’ analysis revealed a focus on “coexistence,” “mitigation,” and “food security.” The literature focused mainly on larger mammals, led by Ethiopian authors, and excluded the social dimensions of HWC. Therefore, identifying conflict-prone species focuses on the social dimensions of coexistence, such as human attitudes towards terrestrial wildlife, and broadening the taxonomic and cultural breadth of HWC is required.